Red Wine Oxidation Characterization by Accelerated Ageing Tests and Cyclic Voltammetry - Deshaies, Stacy; Garcia, Luca; Veran, Frédéric; Mouls, Laetitia; Saucier, Cédric; Garcia, François (Antioxidants, 2021)
In order to obtain information on the oxidative behavior of red wines, oxygen consumption rates and electrochemical changes (cyclic voltammetry) were measured for nine red wines subject to three different accelerated ageing tests: chemical (with hydrogen peroxide), enzymatic (with laccase from Trametes versicolor), and temperature (at 60 °C). Oxidative behavior depended both on the wine sample and accelerated ageing test type. A good correlation was observed between electrochemical parameters of charges for reference/non-oxidized wines, in accordance with their antioxidant capacity, and the variation of charges after enzymatic and temperature tests, meaning that cyclic voltammetry could be used in order to predict these two oxidation tests and reflect the wine sensitivity towards respective oxidation targets. However, it was not possible to predict wine chemical oxidation test based on hydrogen peroxide from the electrochemical measurements.